Monocyte chemoattractant protein-1 (MCP-1) transgenic mice : lessons from cardioprotection against ischemia to autoimmune inflammatory diseases - Martire, Alessandra; Justus Liebig University Giessen (My University, 2002)
To test both, the hypothesis that moderate productions of pro-inflammatory cytokines have a beneficial role in the activation of the cell survival pathway mediated by ischemic preconditioning, and that prolonged cytokines production has a detrimental effect, we have studied transgenic (TG) mice with cardiac myocyte specific overexpression of murine monocyte chemoattractant protein-1 (MCP-1). The resistance to ischemia was studied in adult mice by performing 45-min (with or without injection of the SAPK/JNKs inhibitor D-JNKI1) and 3-day left coronary artery occlusions (CAO)as well as 45-min occlusion followed by 3 days of reperfusion (45-min CAO+3-day R). Quantitative Western blot analyses for TNF-alpha, and SAPK/JNK1/2, ERK1/2, p-38 activity were performed. In addition, immunofluorescence for ubiquitin (ubi, autophagic cell death), complement 9 (C9, necrosis), and MHC class II (autoimmunity) antibodies and TUNEL (apoptosis) method were performed. Infarct size was reduced in TG mice as compared to control (WT) mice after 45-min CAO (14.7±2.6% vs. 52.0±2.4%; p<0.05) and 45-min CAO+3-day R (23.2±1.8% vs. 30.0±1.8%; p<0.05) but not after 3-day CAO. Phosphorylated-(p)-ERKs, and p-p-38 levels were unchanged. P-SAPK/JNK1/2 (expressed by myocytes) and TNF-alpha (expressed by activated inflammatory cells) levels were increased in TG mice compared to WT. In addition, injection of D-JNKI1 partially abrogated the cardioprotective effect observed in untreated TG mice. Finally, quantitative data expressed as percentage of total number of myocytes are reported for TG and WT mice. Ubi: 0.64±0.11 vs. 0; C9: 0.34±0.029 vs. 0; MHC II: 0.27±0.026 vs. 0; TUNEL: 0 vs. 0. Moderate overexpression of MCP-1 causes chronic infiltration and activation of leukocytes resulting in cardioprotection against ischemia through SAPK/JNKs activation in adult mice. Prolonged MCP-1 overexpression induces in old mice cardiomyopathy characterized by different types of cell death: autoimmunity, autophagy, necrosis but not apoptosis, and premature death.

Das Ziel dieser Arbeit war es, die Hypothese zu testen, dass einerseits die moderate Produktion inflammatorischer Zytokine einen positiven Effekt auf die Aktivierung von Signaltransduktionswegen zum Ueberleben von Zellen ausuebt, die durch ischaemische Prekonditionierung vermittelt werden, und dass andererseits die andauernde Produktion von Zytokinen einen schaedigenden Effekt hat. Hierzu wurden transgene Maeuse untersucht, bei denen eine Kardiomyozyten-spezifische Ueberepression des murinen Monozyten-anlockenden Proteins-1 (MCP-1) vorlag. Die Ischaemie-Resistenz wurde bei erwachsenen Maeusen untersucht, indem eine 45-min.(mit oder ohne Injektion des SAPK/JNK-Inhibitors D-JNKI1) bzw. 3-taegige Okklusion der linken Koronararterie (CAO), sowie eine 45-min. CAO gefolgt von 3-taegiger Reperfusion (45-min CAO+3-day R)durchgefuehrt wurde. Zusaetzlich wurde eine quantitative Western-Blot-Analyse von TNF-alpha, SAPK/JNK/2 und der p-38 Aktivitaet durchgefuehrt. Weiterhin erfolgten Immunfluoreszens-Untersuchungen mit Antikoerpern gegen Ubiquitin (ubi, autophager Zelltod), complement 9 (C9, Nekrose) und MHC Klasse II (Autoimmunitaet) und der TUNEL-Methode (Apoptose). Die Infarkt-Groesse bei den transgenen Maeusen war im Vergleich zu den Kontrolltieren nach 45-min. CAO deutlich reduziert (14.7±2.6% vs. 52.0±2.4%; p<0.05), ebenso nach 45-min CAO+3-taegiger R (23.2±1.8% vs. 30.0±1.8%; p<0.05), jedoch nicht nach 3-taegiger CAO. Der Anteil an phosphorylierten (p)-ERKs und p-p-38 blieb unveraendert. Die Expression von p-SAPK/JNK1/2 (exprimiert in Myozyten) und TNF-alpha (exprimiert von aktivierten Entzuendungszellen) war bei den transgenen Maeusen deutlich erhoeht. Die Injektion von D-JNKI1 verringerte teilweise den bei den Kontrollmaeusen beobachteten kardioprotektiven Effekt. Quantitative Daten als Prozent der Gesamtanzahl an Myozyten fuer TG und WT Maeuse wurden erhoben. Ubi: 0.64±0.11 vs. 0; C9: 0.34±0.029 vs. 0; MHC II: 0.27±0.026 vs. 0; TUNEL: 0 vs. 0. Eine maessige Ueberexpression von MCP-1 verursacht chronische Infiltration und Aktivierung von Leukozyten, die in erwachsenen Maeusen durch die Aktivierung von SAPK/JNKs zu einem kardioprotektiven Effekt gegen Ischaemie fuehrt. Die andauernde Ueberexpression von MCP-1 dagegen verursacht bei alten Maeusen eine durch verschiedene Arten von Zelltod wie Autoimmunitaet, Autophagie, Nekrose (keine Apoptose) und vorzeitigen Zelltod charakterisierte Kardiomyopathie.
Mäuse mit transgener Ueberexpression von Monozyten-anlockendem-Protein-1 (MCP-1) : Kardioprotektive Wirkungen gegen Ischaemie aber auch entzuendliche Autoimmunerkrankung
Keywords: transgene Mäuse; Myokarditis; ischaemische Praekonditionierung; Entzündung; Kardiomyopathie; transgenic mice; myocarditis; ischemic preconditioning; inflammation; cardiomyopathy; ddc:610